Association Between Maternal Knowledge of Developmental Stimulation and Toddler developmental status Among Toddlers Aged 12–36 Months - Fitri Handayani; Juliastuti Juliastuti; Hafsah Hafsah (Poltekkes Kemenkes Yogyakarta, 2026)
Toddlerhood (12–36 months) is a critical period of rapid physical, cognitive, language, and socio-emotional development. Maternal knowledge of developmental stimulation is an important factor associated with children's toddler developmental status, yet evidence from community-based settings in Indonesia remains limited. This study aimed to examine the association between maternal knowledge of developmental stimulation and toddler developmental status among toddlers aged 12–36 months attending the Kasih Ibu Integrated Health Post (Posyandu) in Nisam District, North Aceh. A quantitative analytic study with a cross-sectional design was conducted between December 2024 and June 2025. The study involved 36 mothers with toddlers aged 12–36 months who were recruited using a total sampling approach. Maternal knowledge was measured using a 20-item questionnaire (Cronbach's α = 0.82), and toddler development was assessed using the Developmental Pre-Screening Questionnaire (Kuesioner Pra Skrining Perkembangan [KPSP]). Developmental status was categorized as normal or suspected developmental delay (doubtful and delayed). Data were analyzed using the Fisher–Freeman–Halton Exact Test. Most mothers demonstrated good knowledge of developmental stimulation (69.4%), while 16.7% and 13.9% had fair and poor knowledge, respectively. Overall, 69.4% of toddlers had normal developmental status and 30.6% were classified as having suspected developmental delay. The proportion of toddlers with normal developmental status declined from 84.0% among mothers with good knowledge to 50.0% and 20.0% among those with fair and poor knowledge, respectively. A statistically significant association was identified between maternal knowledge and toddler developmental status (exact p = 0.007), with a moderate association strength (C = 0.464). Maternal knowledge of developmental stimulation was significantly associated with toddler developmental status. Enhancing maternal education through Posyandu-based counseling and routine developmental monitoring may support optimal early childhood development.